(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
To address challenges facing public institutions, the Nigerian government established the Tertiary Education Trust Fund (TETFund) with the responsibility of intervening in the funding of infrastructure facilities development, research and staff training. The agency since its establishment has been carrying out lots of interventions in various tertiary institutions across Nigeria especially in the area of infrastructure facilities provision. The study assessed the impact of the Tertiary Education Trust Fund (TETFund) on infrastructural facilities development in tertiary institutions in Nigeria. The study concluded that the Tertiary Education Trust Fund (TETFund) has positively influenced the development of infrastructure facilities in the tertiary institutions in Nigeria. Based on the findings of the study, the paper recommends that the federal government should increase the funding of the Tertiary Education Trust Fund (TETFund) to enable the agency to carry out more infrastructural facilities development across tertiary institutions in the country. There should also be functional Counselling Centers in all tertiary institutions that will ensure sound mental health for students, faculty staff and indeed the entire tertiary institution communities thus create a result oriented teaching and learning environment.